Credit Card Outstanding Balance and Non-Performing Loans in Malaysia : Macroeconomic Determinants and Regulatory Interventions - Chia, Wai Leng (2016)
The credit card debt growth is paradoxical from macroeconomics perspective because it acts simultaneously as stimulus for economic growth and debt crisis. Hence, it is essential to understand the fundamental of household borrowing decision and its mediating market. This led the dissertation back to the fundamental question on understanding the drivers behind the accumulation of debts and the cause of delinquency taking into consideration the significant influence of macroeconomic factors and regulatory interventions at aggregate level. This research focus on emerging market, specifically Malaysia, and taking into consideration the contextual and legal framework differences of the country. One of the advantages of this research is the period understudied comprises sufficient economic variability reflective of Malaysia’s business cycle. The research has reinforced the importance in empirical testing at aggregate level in providing better reflection of the overall economic impact. The result has demonstrated that Consumer Price Index (CPI) is an important determinant that has been neglected in previous researches. The overall result has been consistent with previous literatures except for the contradictory negative correlations in short run results for number of cards in circulation (NOCARD), consumer sentiment index and retrenchment for outstanding balance model; and NOCARD in non-performing loan (NPL) short run model. These contradictions seem to be consistently suggesting the influence of interplay between the liquidity constraints, habit formation and precautionary saving motives. This result provides statistical support to the effectiveness of Bank Negara Malaysia (BNM) interventions to either the outstanding balance or NPL. Nonetheless, it also revealed further improvement in its long term prudential policy is essential in strengthening the economic fundamental of Malaysia.